A Force Sensing Resistor for Monitoring Plantar Force under Foot - Hiemstra, David (My University, 1992)
The needs for obtaining quantitative plantar force information range from basic research into foot function to assisting patients in the use of prosthetic devices. This project reviews present force monitoring techniques, describes the evaluation of a Force Sensing Resistor for monitoring plantar force and proposes a low power portable plantar force monitoring system utilizing an array of force sensing resistors.
Keywords: force; resistor; plantar force